Three days at the brink ebook Fdr's daring gamble to win world war ii. - Baier, Bret (Three Days., 2019)
The Instant New York Times Bestseller "I could not put this extraordinary book down. Three Days at the Brink is a masterpiece: elegantly written, brilliantly conceived, and impeccably researched. This book not only sparkles but is destined to be a classic!" —Jay Winik, bestselling author From the #1 bestselling author and award-winning anchor of Special Report with Bret Baier, comes the gripping lost history of the Tehran Conference, where FDR, Churchill, and Stalin plotted D-Day and the Second World War's endgame. With the fate of World War II in doubt and rumors of a Nazi assassination plot swirling, Franklin Roosevelt risked everything at a clandestine meeting that would change the course of history. November 1943: The Nazis and their Axis allies controlled nearly the entire European continent. Japan dominated the Pacific. Allied successes at Sicily and Guadalcanal had gained them modest ground but at an extraordinary cost. On the Eastern Front, the Soviet Red Army had been bled white. The path of history walked a knife's edge. That same month a daring gambit was hatched that would alter everything. The "Big Three"—Franklin D. Roosevelt, Winston Churchill, and Joseph Stalin—secretly met for the first time to chart a strategy for defeating Adolf Hitler. Over three days in Tehran, Iran, this trio—strange bedfellows united by their mutual responsibility as heads of the Allied powers—made essential decisions that would direct the final years of the war and its aftermath. Meanwhile, looming over the covert meeting was the possible threat of a Nazi assassination plot, code-named Operation Long Jump. Before they left Tehran, the three leaders agreed to open a second front in the West, spearheaded by Operation Overload and the D-Day invasion of France at Normandy the following June. They also discussed what might come after the war, including dividing Germany and establishing the United Nations—plans that laid the groundwork for the postwar world order and the Cold War. Bestselling author and Fox News Channel anchor Bret Baier's new epic history, Three Days at the Brink, centers on these crucial days in Tehran, the medieval Persian city on the edge of the desert. Baier makes clear the importance of Roosevelt, who stood apart as the sole leader of a democracy, recognizing him as the lead strategist for the globe's future—the one man who could ultimately allow or deny the others their place in history. With new details discovered in rarely seen transcripts, oral histories, and declassified State Department and presidential documents from the Franklin D. Roosevelt Library, Baier illuminates the complex character of Roosevelt, revealing a man who grew into his role and accepted the greatest challenge any American president since Lincoln had faced.